THE EFFECT OF WORK DISCIPLINE AND WORK PRODUCTIVITY THROUGH ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN SAMSUNG WTC SURABAYA APOLLO - Adio Astias Hage; Elok Damayanti (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2020)
Samsung Group is one of the largest electronic companies in the world. Founded by Lee Byung Chull on March 1, 1938 in Daegu, Korea. The company operates in 58 countries including Indonesia. Until now, Samsung has also become one of the biggest brands in the world by releasing smart phones that are in the gadget market market. This study aims to analyze the effect of work discipline and work productivity through organizational culture on employee performance at Apollo Samsung WTC Surabaya. This type of research uses a quantitative approach. Data collection uses interviews, observation and questionnaire distribution. Using a non probality method with a purposive sampling approach. The population of this research is the Apollo Samsung WTC Surabaya employees with a sample of 90 respondents. The analytical method used is PLS (Partial Least Square). Based on the results of this study concluded that work discipline, work productivity, organizational culture significantly influence employee performance.